2000
DOI: 10.1016/s0168-0072(00)00018-x
|View full text |Cite
|
Sign up to set email alerts
|

Decidable fragments of first-order temporal logics

Abstract: Accepted versio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
198
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(202 citation statements)
references
References 34 publications
2
198
0
2
Order By: Relevance
“…The decidability of monodic fragments of first-order temporal logic is usually established using 'quasimodels' [12]. Quasimodels for a formula φ have, at each moment in time n, a 'state candidate' which is a collection of possible sets, indexed by elements t in some finite set T , of the formulae ψ in sub x φ such that ψ is true at moment in time n, for some element a (substituting for x) of the domain of a first-order model J(n) that 'realizes' the state candidate.…”
Section: Quasimodelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The decidability of monodic fragments of first-order temporal logic is usually established using 'quasimodels' [12]. Quasimodels for a formula φ have, at each moment in time n, a 'state candidate' which is a collection of possible sets, indexed by elements t in some finite set T , of the formulae ψ in sub x φ such that ψ is true at moment in time n, for some element a (substituting for x) of the domain of a first-order model J(n) that 'realizes' the state candidate.…”
Section: Quasimodelsmentioning
confidence: 99%
“…A test for satisfiability of φ is constructed by encoding the existence of a quasimodel into one of the (decidable) second-order theories of natural numbers with successor functions and monadic predicates S1S or S2S. The exact nature of quasimodels depends on the linear [12] or branching [13], [3] temporal logic of interest. Our aim in this section is to determine when an EMTL pos formula φ has a model for all (temporal) assignments υ in some set of assignments Υ where the assignments to P i ∈ Π vary.…”
Section: Quasimodelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that our model involves both relational terms and a transition system, our analyses require logics that integrate predicate logic and temporal operators. Hodkinson et al have shown [19,20] that such logics have very bad decidability properties, even when the first-order components are restricted to decidable fragments. For example, the monadic fragment of first-order linear temporal logic is undecidable, even restricted to the 2-variable case.…”
Section: Related Workmentioning
confidence: 99%